The Role of School in Raising Awareness of Students About The Dangers of Drug Adicction - Suren Akram Hamanajm (QALAAI ZANIST JOURNAL, 2022)
According to the research plan, the first chapert is dedicated for the dimensions of the study and the definition of concepts, the first is dedicated to the dimensions of the study, in which the research (problems, importance, objectives, and hypothesis) are presented. In the second case, the definition of concepts (role, school, addiction, and drug) is defined. The second chapter is dedicated to exposing the drug addiction of individuals. The third chapter is special to analyzing the phenomenon of drug addiction in the view of two social theories the second axis is the practical aspect of the research, which is presented in the fourth part (the research community, the research sample, the research method, the used statistical framework). The fifth chapter is dedicated to presenting and analyzing the information obtained, and then the results and suggestions are presented.